2009
DOI: 10.1111/j.1600-0625.2009.00926.x
|View full text |Cite
|
Sign up to set email alerts
|

Osteopontin and the skin: multiple emerging roles in cutaneous biology and pathology

Abstract: Osteopontin (OPN) is a glycoprotein expressed by various tissues and cells. The existence of variant forms of OPN as a secreted (sOPN) and intracellular (iOPN) protein and its modification through post-translational modification and proteolytic cleavage explain its broad range of functions. There is increasing knowledge which receptors OPN isoforms can bind to and which signaling pathways are activated to mediate different OPN functions. sOPN interacts with integrins and CD44, mediates cell adhesion, migration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
82
1
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(95 citation statements)
references
References 133 publications
(198 reference statements)
2
82
1
5
Order By: Relevance
“…By performing immunohistochemistry on the primary melanoma specimens, we observed increased OPN protein levels in samples with poor prognosis. Notably, increasing immunostaining was significantly associated with Breslow tumor thickness and metastatic capacity, indicating a role for OPN in melanoma progression [7,24]. However, our protein and gene expression results did not reveal clear relationships in all samples, and on average, we observed that increased OPN mRNA levels were associated with strong antigen positivity.…”
Section: Discussioncontrasting
confidence: 64%
See 2 more Smart Citations
“…By performing immunohistochemistry on the primary melanoma specimens, we observed increased OPN protein levels in samples with poor prognosis. Notably, increasing immunostaining was significantly associated with Breslow tumor thickness and metastatic capacity, indicating a role for OPN in melanoma progression [7,24]. However, our protein and gene expression results did not reveal clear relationships in all samples, and on average, we observed that increased OPN mRNA levels were associated with strong antigen positivity.…”
Section: Discussioncontrasting
confidence: 64%
“…In human malignant melanoma, OPN expression is significantly associated with reduced relapse-free survival and additional histological parameters that are associated with poor clinical outcome [7,24,29,33]. OPN is a prognostic marker in a variety of cancers [30,[39][40][41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…OPN is produced by different cell lines and binds to several integrin receptors and is known to induce cell adhesion, migration, and survival of immune cells including neutrophils, macrophages, T cells, mast cells, and osteoclasts [14].Secreted OPN appears to have a role in the development of psoriasis through inhibiting keratinocyte apoptosis, thereby supporting enhanced epidermal proliferation. OPN promotes vessel formation subsequently supporting the influx of inflammatory cells.OPN has a pro-angiogenic effect on microvascular endothelial cells, and has been involved in the onset of angiogenesis through a mechanism mediated by IL-1 [15].Moreover, there are reports suggest that OPN and MMP-9 may be regulated by TNFα, indicating that they may have a role in the pathogenesis of psoriasis We aimed to assess metabolic syndrome and osteopontin and their associated systemic comorbidities in patients with psoriasis In our study, FBS level was found to benonsignificantlymore in psoriatic cases rather than control. Cholesterol, LDL-c, TG levels weresignificantly elevated, andHDL-c levels were lowerin psoriatic cases than control.…”
Section: Discussion:-mentioning
confidence: 99%
“…OPN secreted by keratinocytes, possibly stimulated through IFN γ from T-cells and OPN from effector T cells attract additional inflammatory cells [15].…”
mentioning
confidence: 99%